The C-terminal repressor region of herpes simplex virus type 1 ICP27 is required for the redistribution of small nuclear ribonucleoprotein particles and splicing factor SC35; however, these alterations are not sufficient to inhibit host cell splicing. - Sandri-Goldin, R M (1995)
Herpes simplex virus type 1 infection results in a reorganization of antigens associated with the small nuclear ribonucleoprotein particles (snRNPs), resulting in the formation of prominent clusters near the nuclear periphery. In this study, we show that the immediate-early protein ICP27, which is involved in the impairment of host cell splicing and in the changes in the distribution of snRNPs, is also required for reassorting the SR domain splicing factor SC35. Other viral processes, such as adsorption and penetration, shutoff of host protein synthesis, early and late gene expression, and DNA replication, do not appear to play a role in changing the staining pattern of splicing antigens. Furthermore, the C-terminal repressor region of ICP27, which is required for the inhibitory effects on splicing, also is involved in redistributing the snRNPs and SC35. During infection or transfection with five different repressor mutants, the speckled staining pattern characteristic of uninfected cells was seen and the level of a spliced target mRNA was not reduced. Infections in the presence of activator mutants showed a redistributed snRNP pattern and a decreased accumulation of spliced target mRNA. Moreover, two arginine-rich regions in the N-terminal half of ICP27 were not required for the redistribution of snRNPs or SC35. Substitution of these regions with a lysine-rich sequence from simian virus 40 large-T antigen resulted in a redistribution of splicing antigens. Unexpectedly, a repressor mutant with a ts phenotype showed a redistributed staining pattern like that seen with wild-type infected cells. During infections with this ts mutant, splicing was not inhibited, as shown in this and previous studies, confirming its repressor phenotype. Furthermore, both the mutant and the wild-type protein colocalized with snRNPs. Therefore, the redistribution of snRNPs and SC35 correlates with ICP27-mediated impairment of host cell splicing, but these alterations are not sufficient to fully inhibit splicing. This indicates that active splicing complexes are still present even after dramatic changes in the organization of the snRNPs.